2018
DOI: 10.7861/clinmedicine.18-1-54
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the efficacy of statins for the treatment of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common type of dementia. Recent studies have assessed the possibility of using statins as treatment for AD. However, their effi cacy is not clear. In this study, we collected the most relevant information about the effi cacy of statins for the treatment of AD. We conducted a systematic literature search using MEDLINE, EMBASE and The Cochrane Library. We included clinical trials, meta-analyses and systematic reviews that analysed the effi cacy of statins in AD. We also extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…However, more recently the LEADe trial of 2010 and the CLASP study of 2011 that assessed the use of statins in AD patients found no net benefit or harm in terms of cognitive decline relative to the placebo group [180,181]. Further support for the idea that statins do not generally benefit AD patients comes from another systematic review [182]. These findings, however, contradict another large study of Medicare beneficiaries which established a beneficial association between statin use and reduced AD incidence in specific populations [183].…”
Section: Statinsmentioning
confidence: 99%
“…However, more recently the LEADe trial of 2010 and the CLASP study of 2011 that assessed the use of statins in AD patients found no net benefit or harm in terms of cognitive decline relative to the placebo group [180,181]. Further support for the idea that statins do not generally benefit AD patients comes from another systematic review [182]. These findings, however, contradict another large study of Medicare beneficiaries which established a beneficial association between statin use and reduced AD incidence in specific populations [183].…”
Section: Statinsmentioning
confidence: 99%
“…In this analysis, the crude model, model 1 (adjusted for dyslipidemia history, total cholesterol, SBP, DBP, and fasting blood glucose), and model 2 (adjusted for model 1 plus obesity, smoking, alcohol consumption, and CCI scores) were determined. The analysis was strati ed by age, sex, income (lower income [1][2][3] and high income [4][5]), and region of residence.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Alzheimer's disease (AD) is not only the most common form of dementia but also the most common cause of neurodegenerative dementia among elderly individuals, accounting for approximately 60% or more of all people with dementia [1]. With an estimated prevalence of 46.8 million cases worldwide in 2015, the number of patients with AD is expected to continue to increase in the coming years [2]. This rapidly increasing disease burden is challenging healthcare and socioeconomic systems worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that there was no significant difference in patients that used statins and those who used placebo. 2,5,7 General practitioner has an essential role in early detection of Alzheimer's disease, recognition of dementia symptoms,referring to diagnostics and specialist consultation, participation in treatment and follow-up of the disease, especially in organization of care and offering permanent help to the patients and support to the family in care of AD patients. He is a part of interdisciplinary team comprising experts of various work fields, specialist consultants, nurses, social workers, psychologists and other experts of various professional profile.…”
Section: Mini Reviewmentioning
confidence: 99%